The impact of foreign debt on economic growth and private investment in Peru: 1980-2008 - Cervantes Grundy, Carlos (2010)
A review of the time series of the Peruvian economic process shows that private investment has an inverse behavior to that of total external debt. Resident economic actors and potential foreign investors, upon observing levels of indebtedness that exceed the ability to pay, reduce investment, which has consequences on the economic growth rate. In the growth equation, introducing the indicator of external debt over GDP squared in order to simulate the Laffer curve, it was found that from 44% of debt over GDP, the indicator is associated with negative growth rates.